2006 8th International Conference on Solid-State and Integrated Circuit Technology Proceedings 2006
DOI: 10.1109/icsict.2006.306675
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sputtered Ta and TaN Films by Spectroscopic Ellipsometry

Abstract: Spectroscopic ellipsometry is emerging as a routine tool for in-situ and ex-situ thin-film characterization in semiconductor manufacturing. For interconnects in ULSI circuits, diffusion barriers of below 10 nm thickness are required and precise thickness control of the deposited layers is indispensable. In this work, we studied single films of tantalum and two stoichiometries of tantalum nitride as well as TaN/Ta film stacks both on bare and oxidized silicon. Spectroscopic ellipsometry from the UV to the NIR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 7 publications
(6 reference statements)
3
13
0
Order By: Relevance
“…3.3. This fact might come from the use of permittivities for Ta, 19 TaN 19 or Cu 20 found in literature. These values were measured by spectrometric ellipsometry.…”
Section: Large Photodiode With Gratingmentioning
confidence: 97%
See 2 more Smart Citations
“…3.3. This fact might come from the use of permittivities for Ta, 19 TaN 19 or Cu 20 found in literature. These values were measured by spectrometric ellipsometry.…”
Section: Large Photodiode With Gratingmentioning
confidence: 97%
“…These values were measured by spectrometric ellipsometry. Deposition and etching method and conditions (substrate, thickness of the layer, temperature... 19 ) differ from one process to another and lead to structural differences which can significantly modify the permittivity of the considered materials. …”
Section: Large Photodiode With Gratingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sputtered TaN films have been widely investigated for their different properties, their optical properties have not been analyzed yet much. Recent studies have shown that spectroscopic ellipsometry (SE) can be used to characterize and measure the thin film thickness because of its fast and non-destructive nature [2,[27][28][29]. Aouadi et al [2] have studied the effects of varying N2 flow rates from 1 to 4 sccm on the structural and optical properties of TaN thin films.…”
Section: Introductionmentioning
confidence: 99%
“…They have found a good agreement of optical properties with narrow-band data available for similar thin films. It was also shown that the optical properties of the films strongly depends with both substrate and film thickness [27]. Ma et al have been studied the temperature-dependent dielectric function of TiN films by SE [28].…”
Section: Introductionmentioning
confidence: 99%